2017
DOI: 10.1002/jcb.26244
|View full text |Cite
|
Sign up to set email alerts
|

Diet and cancer prevention: Dietary compounds, dietary MicroRNAs, and dietary exosomes

Abstract: Cancer is one of main health public problems worldwide. Several factors are involved in beginning and development of cancer. Genetic and internal/external environmental factors can be as important agents that effect on emerging and development of several cancers. Diet and nutrition may be as one of important factors in prevention or treatment of various cancers. A large number studies indicated that suitable dietary patterns may help to cancer prevention or could inhibit development of tumor in cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 135 publications
(281 reference statements)
0
127
0
Order By: Relevance
“…MiRNAs is known as one of important targets for curcumin. These molecules could affect numerous cellular and molecular targets (Banikazemi et al, ; Borujeni et al, ; Golabchi et al, ; Mirzaei, Khataminfar, et al, ; Rashidi, Hoseini, Sahebkar, & Mirzaei, ). It has been found that curcumin could change chemo‐resistance in cancer cells via changing expression of some miRNAs such as miR‐21, miR‐186, miR‐200c, and miR‐27a which might contribute to better treat (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs is known as one of important targets for curcumin. These molecules could affect numerous cellular and molecular targets (Banikazemi et al, ; Borujeni et al, ; Golabchi et al, ; Mirzaei, Khataminfar, et al, ; Rashidi, Hoseini, Sahebkar, & Mirzaei, ). It has been found that curcumin could change chemo‐resistance in cancer cells via changing expression of some miRNAs such as miR‐21, miR‐186, miR‐200c, and miR‐27a which might contribute to better treat (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a natural polyphenol agent, which is isolated from Curcuma longa L. Several curcumin‐based products (ie, capsules, energy drinks, tablets, cosmetics, ointments, and soaps) have been used as drug or spice in different areas such as China, USA, India, and South Africa for centuries . Given that curcumin shows a wide range of pharmacological effects including anti‐inflammatory, anticancer, antioxidant, antimicrobial, and antiangiogenic activities .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are small non‐coding RNAs which act as epigenetic regulators . These molecules play critical roles in regulation of gene expression in the RNA and protein levels . It has been shown that deregulation of microRNAs is associated with initiation and progression of various diseases such as infectious diseases, cardiovascular diseases, diabetes, neurogenerative diseases, and cancer …”
Section: Microrna and Exosome‐based Vaccinementioning
confidence: 99%